Association of vitamins B1 and B2 intake with early-onset sarcopenia in the general adult population of the US: a cross-sectional study of NHANES data from 2011 to 2018 - Yang, Sha; Dong, Zhenyu; Zhao, Jiaqi; Yuan, Lijia; Xiao, Yao; Luo, Xing; Zhao, Zhuyang; Kang, Xia; Tang, Kanglai; Chen, Ming; Feng, Liu (Frontiers in Nutrition, 2024)
Background Early-onset sarcopenia refers to the progressive loss of muscle mass and function that occurs at an early age. This condition perpetuates the vicious cycle of muscle loss and is associated with adverse outcomes. It is important to identify the contributing factors for early intervention and prevention. While diet is known to impact muscle mass, the association of B vitamins with early-onset sarcopenia remains unexplored. Objectives To investigate the association of B vitamins intake with early-onset sarcopenia risk in a cross-sectional study. Methods We conducted data analysis on a total of 8,711 participants aged between 20 and 59 years who took part in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. Early-onset sarcopenia was defined as a SMI measured by DXA that was one standard deviation below the sex-specific mean of the reference population. B vitamins intake (B1, B2, B3, B6, B9, and B12) was assessed by 24-h dietary recall. We used weighted multiple logistic regression and RCS models to estimate the OR and 95% CI of sarcopenia by B vitamins intake, adjusting for demographic, physical, lifestyle, comorbidities, and nutritional covariates. Results Higher intake of vitamin B1 was associated with a 22% lower sarcopenia risk (OR = 0.78, CI = 0.63–0.97, p = 0.022), and higher intake of vitamin B2 with a 16% lower risk (OR = 0.84, CI = 0.74–0.97, p = 0.012) in both genders. Gender-specific analyses showed a 28% reduction in sarcopenia risk among males with each additional mg of vitamin B1 intake (OR = 0.72, CI = 0.52–0.97, p = 0.038), and a 26% decrease among females with each additional mg of vitamin B2 intake (OR = 0.74, CI = 0.57–0.96, p = 0.021). No significant differences were found between vitamin B2 and males, or between vitamin B1 and females. The RCS model suggested a nonlinear relationship between vitamin B2 intake and sarcopenia risk (POverall = 0.001, PNonlinear = 0.033), with a plateau effect above 3 mg/d. Conclusion Higher intake of vitamin B1 and B2 may lower the risk of early-onset sarcopenia, with gender differences. This suggests the potential of nutritional intervention by increasing these vitamins intake through diet and supplements. Further research is warranted to elucidate the mechanisms and design targeted interventions.